Effect of varnish coating agent application on surface hardness of glass ionomer cement after immersion in carbonated drinks - Arsanti, Natasya; Megantoro, Aryo; Meidyawati, Ratna (Universitas Padjadjaran, 2023)
ABSTRACTIntroduction: Glass ionomer cement is a material for treating dental caries. The disadvantage of glass ionomer cement is that if it comes into contact with acids before maturation, there will be a decrease in mechanical properties which is indicated by a decrease in surface hardness. Surface hardness has a relationship with aesthetics and resistance to scratches that can cause fractures. Coating agents like varnishes are required for glass ionomer cement to protect them from liquids with low pH level, such as carbonated drinks. Unfortunately many dentists neglected this procedure. The purpose of this research was to compare the surface hardness of glass ionomer cement which is protected and not protected by coating agent when its maturation is in contact with acids, to emphasize the importance of this procedure. Methods: This research was a laboratory experimental study. Samples consist of 24 glass ionomer cement specimens (GC Fuji IX GP EXTRA). Glass ionomer cement specimens were divided into 4 treatment groups. The first group was not applied with varnish and stored without immersion, the second group was applied with varnish and stored in artificial saliva, the third group was applied with varnish and soaked in carbonated drinks, and the last group was not applied with varnish and was immersed in carbonated drinks. The data that has been collected was processed and analyzed using the computer-based application IBM SPSS Statistics version 23.0. Results: There was a significant increase in the surface hardness of glass ionomer cement in all treatment groups. There was a significant difference in the mean surface hardness of glass ionomer cement after immersion in carbonated drinks between the groups that were applied with varnish coating agent and that without application of varnish coating agent. Conclusion: The surface hardness of glass ionomer cement restoration which was applied with varnish coating agent has a higher value compared to those not applied with varnish coating agent after immersion on carbonated drinks.Keywords: carbonated drinks, glass ionomer cement, microhardness test; saliva, varnish coating agent